Physiological and self-reported disgust reactions to obesity. Issue 3 (3rd April 2018) - Vartanian, Lenny R.; Trewartha, Tara; Beames, Joanne R.; Azevedo, Suzanna M.; Vanman, Eric J.
ABSTRACT: There is accumulating evidence that disgust plays an important role in prejudice toward individuals with obesity, but that research is primarily based on self-reported emotions. In four studies, we examined whether participants displayed a physiological marker of disgust (i.e. levator labii activity recorded using facial electromyography) in response to images of obese individuals, and whether these responses corresponded with their self-reported disgust to those images. All four studies showed the predicted self-reported disgust response toward images of obese individuals. Study 1 further showed that participants exhibited more levator activity to images of obese individuals than to neutral images. However, Studies 2–4 failed to provide any evidence that the targets' body size affected levator responses. These findings suggest that disgust may operate at multiple levels, and that the disgust response to images of obese individuals may be more of a cognitive-conceptual one than a physiological one.